Restauração de dentes tratados endodonticamente: ensaio clínico randomizado e revisão sistemática com metánalise - Onofre, Rafael Sarkis (2012)
The best way to restore endodontically treated teeth has been discussed in the literature because some factors can influence the post selection and the final restoration. Two of the most used intra-radicular posts are cast metal posts and glass fiber posts. Moreover, there is a large variability of in vitro studies that evaluate the use of different resin cement and the alterations of technique and the influence in the bond strength of glass fiber posts. The aims of the study were to compare the survival of two types of dental posts used to restore endodontically treated teeth with great damage of coronal walls and verify through a systematic review if there is difference on bond strength of glass fiber posts to dentin between self-adhesive and regular resin cements. Systematic review: In vitro studies that investigated the bond strength of glass fiber post luted with self-adhesive (RC) and regular (RC) were selected. Global comparison between self-adhesive (RC) and regular resin cement was performed. Two subgroup analyses were performed: self-adhesive resin cement x regular resin cement (etch-and-rinse adhesive), self-adhesive resin cement x regular resin cement (self-etch adhesive). The three analyses performed showed favorable results to self-adhesive resin cement. Clinical trial: The teeth were randomly allocated into two groups depending on the post used: glass fiber or cast metal post. Fifty-four (45 women) patients and 72 teeth were evaluated up to 3 years and the survival probabilities were 97.1% and 91.9% to cast metal posts and glass fiber posts. Four failures were observed, 2 glass fiber posts debonding (premolar and anterior tooth), 1 glass fiber post debonding associate with root fracture and 1 root fracture with a cast metal post. We can conclude that in vitro literature seems to suggest that the use of self-adhesive cement could help to achieve higher bond strength of GFPs to the root canal and after 3 years of follow up, both posts presented the same clinical performance and